Implementation strategies to increase human papillomavirus vaccination uptake for adolescent girls in sub-Saharan Africa: A scoping review protocol. - Mwansa Ketty Lubeya; Mulindi Mwanahamuntu; Carla Chibwesha; Moses Mukosha; Mercy Monde Wamunyima; Mary Kawonga (PLoS ONE)
Introduction The human papillomavirus (HPV) is sexually transmitted and infects approximately 75% of sexually active people early in their sexual life. Persistent infection with oncogenic HPV types can lead to malignant conditions such as cervical cancer. In 2006, the World Health Organisation approved the use of an efficacious HPV vaccine for girls aged 9 to 14 to prevent HPV-related conditions. Despite the HPV vaccine being available for about 15 years, dose completion remains as low as 20% in sub-Saharan African (SSA) countries implementing the vaccination program compared to 77% in Australia and New Zealand. A fraught of barriers to implementation exist which prevent adequate coverage. Achieving success for HPV vaccination in real-world settings requires strategies to overcome implementation bottlenecks. Therefore, a better understanding and mapping of the implementation strategies used in sub-Saharan Africa to increase HPV vaccination uptake is critical. This review aims to identify implementation strategies to increase HPV vaccination uptake for adolescent girls in sub-Saharan Africa and provide a basis for policy and future research, including systematic reviews to evaluate effective strategies as we accelerate the elimination of cervical cancer. Materials and methods This scoping review will consider studies pertaining to implementation strategies to increase HPV vaccination uptake for adolescent girls in sub-Saharan Africa. Studies targeted at different stakeholders to increase adolescent vaccine uptake will be included. Studies using interventions not fitting the definition of implementation strategies as defined by the refined compilation of implementation strategies from the Expert Recommendations for Implementing Change project will be excluded. MEDLINE (via PubMed), Embase, CINAHL (via EBSCO), Scopus and Google Scholar will be searched. Two independent reviewers will screen titles and abstracts for studies that meet the review's inclusion criteria, and the full text of eligible studies will be reviewed. Data will be extracted from eligible studies using a structured data charting table developed by this team for inclusion by two independent reviewers and presented in a table and graphical form with a narrative summary.